Bio-ecological study of the water mites (Acari: Hydracarina) of the pond of El-Goureate in the National Park of El-Kala (North-East of Algeria) - Messikh, Samia (2021)
This study aimed to present faunistic and ecological data on aquatic mites living in small permanent basins and selected lakes in the El-Kala National Park (Northeast of Algeria). Thus, this study shows the research of Hydracarina in the park comprehensively over the two years. We have identified the living Hydracarina species in the semi-temporary study site at Goureate pond.  The existence of an unknown and interesting Hydracarina fauna has been revealed. The collection of specimens revealed the presence of 9 species divided into 5 families.  The identification required the study of ecological indices and the measurement of physicochemical parameters (temperature, humidity). The results of the univariate analysis of variance test fixed model, applied to each of the 9 physicochemical variables and a variable related to the number of Hydracarina, for two years. The results showed a very highly significant difference for water temperature and atmospheric temperature and a just significant difference for the number of Hydracarina, while no significant difference for pH, humidity, conductivity, NO-2, PO-4, NH+4 is registered, and the study of the abundance of the identified species in the four stations during the four seasons.